Two more new species of Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the northern Western Ghats, Maharashtra, India - Khandekar, Akshay; Thackeray, Tejas; Agarwal, Ishan (Zootaxa, 2019)
We describe two new species of the gekkonid genus Cnemaspis from the northern Western Ghats in Maharashtra, India. Cnemaspis amba sp. nov. and C. koynaensis sp. nov. are members of the C. girii clade and differ genetically from each other and other members of the clade by 7.9–19.6 % uncorrected ND2 sequence divergence. The two new species are also morphologically distinguishable from all regional congeners on the basis of condition of spine-like scales on flanks, heterogeneity of dorsal pholidosis, number of dorsal tubercle rows, number of tubercles in paravertebral rows, femoral pores, number of poreless scales between femoral pores in the precloacal-femoral scale row, and keeling and size of sub-caudal scales. Cnemaspis amba sp. nov. differs from C. koynaensis sp. nov. in lacking  spine-like scales on flanks and in the number of longitudinal ventral scales and  ventral scales across mid-body. Both species are known only from their mid-elevation (~800 m asl.) type localities. Discovery of two new species increases the total species of Northern Western Ghats (NWG) Cnemaspis to ten. Specific status of numerous genetically divergent lineages needs to be evaluated and it is likely that many more species remain to be discovered from the poorly explored NWG, which are typically considered low in species diversity relative to more southern regions. We also provide a table describing major diagnostic characters across all NWG Cnemaspis species and corrected type locality data for three recently named species—Cnemaspis ajijae, C. limayei and C. mahabali.